Farmer's perception and knowledge on landslide occurrences in Beruk Village, Karanganyar Regency, Central Java. Issue 1 (March 2020) - Aditya, B; Amri, I; Putri, R F
Abstract: Karanganyar Regency is one of the most prone area to landslides in Central Java. According to DIBI records, 77 of the 149 types of natural disasters that occurred in this area were landslides during 2008-2018 and the trend tends to increase. In disaster management, the ability of the community to reduce the risk of landslides is reflected in capacity. The objective of this study is to know the farmers understanding on landslide factor, landslide occurrences and impact, and landslide mitigation in Beruk Village, Karanganyar Regency. The data was collected by interview to 109 farmers household, and the analysis was conducted by descriptive analysis. The result shows that the landslide is mostly caused by heavy and long duration of rain, indicator for landslide is ground cracks, and the mitigation mechanism is based on local knowledge of farmers such as managing irrigation system, planting trees, and managing land utilization. In Beruk Village, disaster management process is more to be responsive rather than preventive and the knowledge of farmers on land management play an important role in disaster risk reduction.